On the Savéant's Concerted/Stepwise Model. The Electroreduction of Halogenated Naphthalene Derivatives as a Case Study. Issue 22 (19th November 2021) - Stefani, Andrea; Giurlani, Walter; Bonechi, Marco; Marchetti, Andrea; Preda, Giovanni; Pasini, Dario; Innocenti, Massimo; Fontanesi, Claudio
Abstract: The electroreduction mechanism of 1‐Br‐2‐naphtol and 1‐I‐2‐naphtol, and of two inherently chiral BINOL derivatives ([1, 1′‐Binaphthalene]‐2, 2′‐diol, 6, 6′‐dibromo and 1, 1′‐Binaphthalene, 6, 6′‐dibromo‐2, 2′‐dimethoxy; in the following named P1 and P2, respectively), is characterized by means of an integrated electrochemical and theoretical approach. The experimental characterization is based on cyclic voltammetry measurements. The experimental results indicate that the carbon halogen bond dissociates, following the electron uptake, with the formation of an insoluble final product (electro‐polymerization). The reduction mechanism is assessed and disassembled at a molecular level by using DFT based quantum mechanical calculations. Both steady state, equilibrium, and kinetic (molecular dynamics, MD, DRC calculations) properties are calculated. A consistent picture is obtained by the comparison between experimental and theoretical results, indicating that the carbon‐halogen bond dissociates following the first electron uptake, with a stepwise mechanism. Abstract : The electroreduction of 1‐Br‐2‐naphthol is shown to be a not‐additive process with respect to the results obtained with two structurally related chiral [1, 1′‐Binaphthalene]‐2, 2′‐diol, 6, 6′‐dibromo and 1, 1′‐Binaphthalene, 6, 6′‐dibromo‐2, 2′‐dimethoxy compounds. The 1‐Br‐2‐naphtol reduction is accompanied by the carbon bromine dissociation, eventually producing a film due to a fast radical‐radical cross reaction. The film formation is not observed in the BINOL‐like chiral halogen‐derivatives.